2017 32nd IEEE/ACM International Conference on Automated Software Engineering (ASE) 2017
DOI: 10.1109/ase.2017.8115624
|View full text |Cite
|
Sign up to set email alerts
|

Detecting fragile comments

Abstract: The development lifecycle of a software system demands incessant improvements in the source code of a system to maintain its high quality with improved performance and code readability.Refactoring is a common software development practice that reshapes the internal structure and non-functional properties of a system without modifying its core functionality. Many simple refactorings like renaming code elements, extracting a snippet from large method to form new method etc. can be performed with the help of auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Given the relevance of code comments for program comprehension and maintenance activities (Woodfield et al 1981;Tenny 1985;Tenny 1988;Hartzman and Austin 1993;de Souza et al 2006;Lidwell et al 2010;Cornelissen et al 2009), researchers have analyzed comments to detect low-quality comments (Steidl et al 2013;Liu et al 2015), identify existing inconsistency between comments and their related code elements (Ratol and Robillard 2017;Wen et al 2019;Stylos et al 2009;Petrosyan et al 2015;Zhou et al 2017), and they have examined the co-evolution of comments and code (Jiang and Hassan 2006;Fluri et al 2007;Fluri et al 2009;Ibrahim et al , 2012). However, very few studies have focused on analyzing the information embedded in the source code comments (Padioleau et al 2009;Haouari et al 2011;Steidl et al 2013;Pascarella and Bacchelli 2017;Zhang et al 2018), and none of them specifically analyzed class comments, or to what extent these class commenting practices adhere to the coding style guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Given the relevance of code comments for program comprehension and maintenance activities (Woodfield et al 1981;Tenny 1985;Tenny 1988;Hartzman and Austin 1993;de Souza et al 2006;Lidwell et al 2010;Cornelissen et al 2009), researchers have analyzed comments to detect low-quality comments (Steidl et al 2013;Liu et al 2015), identify existing inconsistency between comments and their related code elements (Ratol and Robillard 2017;Wen et al 2019;Stylos et al 2009;Petrosyan et al 2015;Zhou et al 2017), and they have examined the co-evolution of comments and code (Jiang and Hassan 2006;Fluri et al 2007;Fluri et al 2009;Ibrahim et al , 2012). However, very few studies have focused on analyzing the information embedded in the source code comments (Padioleau et al 2009;Haouari et al 2011;Steidl et al 2013;Pascarella and Bacchelli 2017;Zhang et al 2018), and none of them specifically analyzed class comments, or to what extent these class commenting practices adhere to the coding style guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Preprocessing variables' identifiers and comments is an essential step for our detection approaches. For this, we followed part of the steps proposed by Ratol et al [17] for preprocessing both variables' identifiers and the text of comments, while we create our own prepossessing steps to suit our matching techniques. We present these steps as following:…”
Section: A Preprocessingmentioning
confidence: 99%
“…Six project repositories were used to evaluate our proposed approaches, motivated by previous work of Ratol et al [17] to detect fragile comments. These projects (see Table III) were selected because they were used in Ratol et al's work [17] and showed several advantages such as their availability as open-source, a diversity of application domains, and being well-commented. To allow further investigation, the six projects were cloned locally to ease the process to analysing them.…”
Section: A Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations